Psychometric properties of the Persian short form of the Stigma of Suicide Scale - Jafari, Alireza; Mokhtari, Ali Mohammad; Moshki, Mahdi; Rahmani, Fatemeh; Naddafi, Fatemehzahra; Nejatian, Mahbobeh (Frontiers in Psychiatry, 2024)
Objective: Suicide stigma is a major obstacle to suicide prevention, resulting in a decrease in mental help seeking. This study aimed to survey the psychometric characteristics of the Persian short form of the Stigma of Suicide Scale (SOSS). Methods: This psychometric study was conducted on 956 people (EFA = 399 samples, CFA = 557) in 2022 to evaluate the validity (face, content, and structure validity) and reliability (Cronbach’s alpha coefficient, McDonald Omega coefficient, and intraclass correlation coefficient) of the SOSS. The structural validity of the scale was assessed by confirmatory factor analysis (CFA) and exploratory factor analysis (EFA). Results: The score of S-CVI/ Ave and CVR for SOSS were 0.982 and 0.921, respectively. In the EFA section, three factors with eigenvalues above one were shown, and 60.60 % variance of the scale was explained by these factors, and one question was eliminated due the factor loading less than 0.4 and also moving to an irrelevant factor. Finally, based on the goodness-of-fit indices (such as RMSEA = .077, CFI= .902, IFI= .903, GFI= .915), the Persian short form of SOSS was approved with 15 items and three factors of Glorification/Normalisation (4 items), Stigma (7 items), Isolation/Depression (4 items). The McDonald Omega coefficient, Cronbach’s alpha coefficient, and ICC for SOSS were 0.841, 0.834, and 0.881, respectively. Conclusion: In this study, the Persian short form of the SOSS was approved with 15 items and 3 factors, and this scale is an appropriate instrument for determining the status of suicide stigma among general population.